(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
The primary drug delivery methods are intravenous (IV), intramuscular (IM), intranasal (IN), intradermal (ID), transdermal and oral administration. Other routes, such as ocular delivery, have also been developed for localized, site-specific drug administration without unwanted systemic side effects. Each mode of administration poses particular barriers in terms of drug delivery. Furthermore, medications can be integrated into delivery devices, which significantly contributes to therapeutic efficacy, drug preservation, and targeting. We initially present the overview of the many administration methods in this review before concentrating upon oral delivery systems as being the most appealing route. We explain the main challenges associated with such methods and review the most recent solutions developed to address them.